Porous media : fluid transport and pore structure - Dullien, F. A. L. (Academic Press, 1992)
This book examines the relationship between transport properties and pore structure of porous material. Models of pore structure are presented with a discussion of how such models can be used to predict the transport properties of porous media. Portions of the book are devoted to interpretations of experimental results in this area and directions for future research. Practical applications are given where applicable, and are expected to be useful for a large number of different fields, including reservoir engineering, geology, hydrogeology, soil science, chemical process engineering, biomedical engineering, fuel technology, hydrometallurgy, nuclear reactor technology, and materials science. Key Features * Presents mechanisms of immiscible and miscible displacement (hydrodynamic dispersion) process in porous media * Examines relationships between pore structure and fluid transport * Considers approaches to enhanced oil recovery * Explores network modeling and perolation theory.